Actitud del varón frente a la planificación familiar en la localidad del Centro Poblado Nueve de Abril Enero – Abril 1994 - Villacorta Vela, Gladis (1994)
The study is an explanatory trial with prospective data collection performed in the village Nine male April 13 Centro - 60 years, for which indirect surveys were used with mixed questions. The sample consisted of 983 men, almost 100% of the male population within the age range considered. The aim of this study was to demonstrate the attitude adopted by man before the Family Planning. After the respective statistical analysis has led to the following conclusions: 1. 70.9% of men of the town center Nueve de Abril use protection. 2. 52.0% of men assume an attitude of indifference to family planning, giving responsibility to the women, and 1.5%, negative and opposition to the use of contraceptives attitude. 3. The level of education and age are factors that modulate the behavior towards family planning and contraceptive use. 4.- plus couples used contraceptive methods are the pill (22.2%) and the IUD (21.3%) and female sterilization (10.8%). 5. The methods used by the man are the condom (72.3%.) Followed by the rhythm and periodic abstinence (19.9%), thirdly the Withdrawal (7.5%) and lastly vasectomy (0.3%) . 6. The 77.7% of men qualify to condoms as a good method, 77.6% believe how bad the rhythm method of contraception. 7. 72% of men who do not use any contraceptive method intend to use it in the future.